Urban energy landscape in practice: Architecture, infrastructure and the material culture of cooling in post-reform Chongqing, China - Kobi, Madlen (Urban Studies, 2024)
Until the 1990s and the spread of air-conditioning, cooling down during the hot, humid and windless summers in the city of Chongqing (Southwest China) was mainly practised outdoors: sleeping on the rooftops of multistorey buildings, playing mah-jongg in t
Keywords: Electricity; Path Dependency; Thermal Practice; Urban Climate; Built Environment